Das solare Signal im Nordatlantikraum und die Variabilität seiner räumlichen Struktur - Dettling, Nicolas (2018)
The influence of the 11-year solar cycle on the North Atlantic winter climate is investigated using a chemistry climate model simulation with the CESM climate model. The simulation consists of 999 model years and encompasses a far greater number of solar cycles then it is the case in previous studies. Therefore, the data for the first time allow an examination of the effects of the solar cycle on the climate system over a larger time frame. External forcing is thereby held constant on preindustrial levels in order to concentrate on the system's internal response to the chosen solar forcing. Wavelet analysis of the FlO. 7cm radio flux parameter and the first Principal Components of winter sea level pressure in the North Atlantic shows a persisting connection between the solar cycle and the atmospheric circulation patterns over the whole simulation period. Wavelet coherence with the solar forcing is thereby found to change between combinations of the teleconnection patterns North Atlantic Oscillation (NAO), East Atlantic Pattern (EA) and Scandinavia Pattern (SCAND). A period of 50 years showing wavelet coherence between the solar signal and a combination of NAO and EA is then examined in further detail. Particular focus lies on the physical mechanism, by which the solar signal is communicated through the atmosphere. Lead-lag correlations between the F10.7cm solar radio flux parameter and temperature, zonal wind and geopotential height differ from distributions seen in studies with exclusive dominant solar influence on the NAO. Especially the pole- and downward propagation of a positive zonal wind signal corresponding to the top-down mechanism can not be identified. Instead, the solar cycle is observed to project onto a positive EA phase as well as a negative NAO phase in higher latitudes. The strongest response of the circulation patterns to the solar cycle is observed two years after the solar maximum. This is attributed to the conservation of the solar signal in North Atlantic winter thermoclines and persisting ...